Ovilyra, a new genus of leucosiid crab (Crustacea: Decapoda: Brachyura) from the West Pacific - Ng, Peter K. L. (Zootaxa, 2021)
The identities of two species of shallow water Southeast Asian and southern Chinese leucosiid crabs Philyra fuliginosa Targioni-Tozzetti, 1877, and P. olivacea Rathbun, 1909, are clarified; and shown to be synonyms. A new genus, Ovilyra, is established for P. fuliginosa, and it is easily distinguished from Philyra s. str. as well as allied genera by possessing an elongate carapace, a narrow and slender male pleon with somites 1 and 2 articulate, and a male first gonopod which has the distal quarter sharply bent with a well developed subdistal process.